2021
DOI: 10.1007/jhep05(2021)120
|View full text |Cite
|
Sign up to set email alerts
|

W-infinity symmetry in the quantum hall effect beyond the edge

Abstract: The description of chiral quantum incompressible fluids by the W∞ symmetry can be extended from the edge, where it encompasses the conformal field theory approach, to the non-conformal bulk. The two regimes are characterized by excitations with different sizes, energies and momenta within the disk geometry. In particular, the bulk quantities have a finite limit for large droplets. We obtain analytic results for the radial shape of excitations, the edge reconstruction phenomenon and the energy spectrum of densi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Abstractly, one can also think of (18) as the logarithmic time derivative of the path of deformations g t (ϕ). One can then plug (18) in the Lie algebra operator (12) and use the Berry phase…”
Section: Berry Phases From Circle Deformationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Abstractly, one can also think of (18) as the logarithmic time derivative of the path of deformations g t (ϕ). One can then plug (18) in the Lie algebra operator (12) and use the Berry phase…”
Section: Berry Phases From Circle Deformationsmentioning
confidence: 99%
“…In the case of 1D deformations, we exhibited this with eq. ( 19), involving the 1D vector field (18) and its flow g t . It is therefore essential to become acquainted with the 2D version of these objects, i.e.…”
Section: Divergence-free Vector Fields and Incompressible Flowsmentioning
confidence: 99%
See 2 more Smart Citations
“…Richer algebraic structures in QH systems other than the Heisenberg algebra of the ladder operators were proposed by Cappelli, Trugenberger, and Zemba in 1993, who found that the product of ladder operators could form a W ∞ -algebra, and the similar algebra was generalized to FQH afterward [103][104][105][106][107]. In fact, the GMP algebra of density operators is isomorphic to a W ∞ -algebra as well, which reveals their nature as area-preserving deformations of the incompressible phase and partially explains why there can be analytic expressions of physical quantities for the SMA wave function including those derived in this thesis (more details can be found in Appendix.B).…”
Section: Harvest Time: 1993 -2003mentioning
confidence: 99%